Ян Амос Коменський і розвиток педагогічної думки України в XVII ст. - Антонюк, Галина (Видавництво Львівської політехніки, 2012)
В контексте педагогики Возрождения и Нового времени в статье проанализированы педагогические взгляды Яна Амоса Коменского; сделано попытку сопоставительного анализа идей Коменского и педагогической практики братских школ Украины и Белоруссии; проанализированы общие черты педагогических взглядов чешского ученого и украинских просветителей; подчеркнуто влияние идей Яна Амоса Коменского на развитие образования в славянском и общеевропейском пространстве. The article analyses pedagogical views of Jan Amos Comenius in the context of the Renaissance pedagogy and pedagogy of Early Modern Period. It conducts comparative analysis of Comenius’ ideas and pedagogical practice of brotherhood schools in Ukraine and Belarus, determines similarities common for the ideas of Czech scholar and Ukrainian educators. The article also defines influence of Jan Amos Comenius’ ideas on the development of education in the Slavic and European space.
Ян Амос Коменский и развитие педагогической мысли Украины в XVII ст.
Jan Amos Comenius and the development of pedagogical thought in Ukraine in the XVII – XVIII centuries
Keywords: Коменский Ян Амос; братские школы Украины; украинская педагогическая культура; взаимовлияние культур; John Amos Comenius; brotherhood schools in Ukraine; Ukrainian pedagogical culture; cultures interaction